Pengaruh Modifikasi Permainan Invasi Terhadap Peningkatan Keterampilan Motorik dan Self-Satisfaction Siswa Sekolah Dasar - Muhammad Mizan Rakhmanda; Ricky Wibow; Mukhlisin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
of motor skills and self-satisfaction among elementary school students. The method used was a pre-experimental design with a one-group pretest-posttest design, involving 46 fifth-grade students from SDN 6 Arjawinangun selected through random sampling. The instrument for measuring motor skills used the Fundamental Motor Skills in Sport (FMS), while self-satisfaction was measured using the Satisfaction with Life Scale-Children (SWLS-C). The intervention consisted of a modified futsal invasion game program administered over 12 sessions at a frequency of three times per week. Data analysis included descriptive statistics, the Shapiro-Wilk normality test, Levene’s Test for homogeneity of variances, and hypothesis testing using a paired-sample t-test. The results showed an improvement in motor skills with an N-Gain of 78.23%, classified as high effectiveness, as well as an increase in self-satisfaction with an N-Gain of 44.07%, classified as moderate effectiveness. Both variables yielded a significance value of 0.000. Thus, it can be concluded that the modification of the invasion game has a significant effect on the improvement of motor skills and self-satisfaction among elementary school students simultaneously and measurably. Keywords: Motor Skills, Invasion Game Modification, Self-Satisfaction